COT-08 Analysis of prognosis of biopsy/partial resection cases of malignant glioma. (28th November 2020) - Yamamoto, Yohei; Teshigawara, Akihiko; Takei, Jun; Tanaka, Toshihide; Akasaki, Yasuharu; Murayama, Yuichi
Abstract: Introduction: Malignant glioma is the most common and aggressive primary brain tumor and requires multimodality treatment. Regarding surgical treatment, it is desirable to achieve maximum resection while considering function preservation. There is consensus that the survival prognosis is prolonged in gross or subtotal resection. However, there are cases in which biopsy or partial resection is performed due to the spread of lesions at the time of onset, underlying diseases, and social background. The purpose of this study was to retrospectively analyze the cases of malignant glioma at our university and to find out the factors related to the prognosis of cases in which removal was insufficient. Target: 55 cases of malignant glioma treated at our university since 2013 who underwent biopsy or partial resection. Method: Overall/progression-free survival period is the end point, and parameters are age, bevacizumab use, pathological diagnosis, photodynamic diagnosis use at operation, immunotherapy, ventricular invasion, contralateral invasion, sex, preoperative Performance Status (PS), postoperative PS, left or right, navigation use, steroid use, anticonvulsant drug type, radiation, IDH mutation, 1p19q co-deletion, MGMT methylation, TERT mutation, p53 mutation, biopsy or partial resection. After narrowing down the evaluation items by univariate analysis(Logrank test), multivariate analysis(Cox proportional hazard model)was performed. Result: The univariate analysis was significant in 5 items including bevacizumab use, radiation therapy, levetiracetam use, postoperative PS70 or higher, and partial resection instead of biopsy. Multivariate analysis detected two statistically significant differences, bevacizumab use and post-operative PS70 and above. There was no difference in the timing of bevacizumab use. Consideration: In poorly resection cases, the weight of postoperative treatment is high, so continuity of treatment and selection of postoperative treatment are important, and maintenance of ADL and use of bevacizumab are significant among them.